PSYCHEDELICS IN PSYCHIATRY - OVERVIEW OF PSILOCYBIN RESEARCH - Anna Blazhkova; Magdalena Czaja; Hanna Sitka; Sven Solisch; Anna Susłow; Ewa Szczęsna (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Recently, there has been a significant increase in interest in the use of psychedelics for various psychiatric conditions. Psilocybin is receiving particular attention as a psychoactive substance with significant therapeutic potential. Recent research focuses on its possible benefits in the treatment of major depressive disorders (MDD) and anorexia nervosa (AN). Purpose of the study: This study aims to investigate the therapeutic potential of psilocybin in treating MDD and AN by analyzing its mechanism of action, clinical trials results and further implications of PAT. Materials and methods: An overview of 26 articles sourced from PubMed and open-access databases was conducted, with a focus on randomized controlled trials, neurobiological mechanisms and also exploratory research. Conclusions: Psilocybin and PAT demonstrated significant antidepressant effects, enhancing neuroplasticity, connectivity and cognitive flexibility. While evidence in MDD is significantly more established, preliminary findings in AN are promising, but still require further controlled clinical trials. Psilocybin represents a novel approach to treatment of MDD and AN.